Pengaruh pemangkasan terhadap pertumbuhan: percabangan dan pembesaran bonggol tiga kultivar kamboja Jepang (Adenium Arabicum) - Yayat Rochayat Suradinata; Adinda Cikal Amalia; Anne Nuraini (Universitas Padjadjaran, 2017)
Ornamental plant of Adenium arabicum has a selling value and a high aesthetic value. The beauty of the exotic stump and branching lots are characteristic that differentiates it from other species of Adenium. However, to get a lot of branching and stump enlargement require a long time, so that should an effort to speed up the desired form A. aracium, that is by pruning. This research aimed to determine the effect of pruning on growth, that is branching and stump enlargement three cultivars of A. arabicum. Experiment as done on April until June 2016 at Ciparanje Experimental Station, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang, West Java. The experiment used Factorial Randomized Block Design with three cultivars (Yak Saudi, RCN, and Thai Socotranum) and pruning (without pruning, pruning 7segments, and pruning 14 segments), with three replications. The result of the experiment showed that there was interaction between three cultivars and branching increased the diameter of the stump A. arabicum at 6 weeks after pruning. Interactions that occur, that was between Yak Saudi cultivars with without pruning. Treatment on three cultivars don’t showed different effects. Pruning 14 segments showed the best effect to increased the number of branches, branch length, number of leaves and leaf area on the plant of A. arabicum. Keywords: Adenium arabicum, pruning, RCN, Thai Socotranum, Yak Saudi.